An Exploratory Study of the Critical Need for School Health Programs in Lebanon - Khayrazad kari Jabbour (Intelektual Pustaka Media Utama, 2013)
Abstract Schools play a vital role in establishing healthy behavior patterns among young people which carry these patterns into adulthood. This article explores and collects information about school health programs and health practices in Lebanese schools. The investigation goal is to provide baseline information to school policy makers, administrators, and educators as they plan and implement coordinated school health policies and educational programs that can promote healthy behaviors among the Lebanese youth. Data for the study was obtained from extensive literature reviews and questionnaire surveys of school principles; in addition, interviews were added to the data results. The survey was conducted in the spring of year 2013.